Norovirus‐associated gastroenteritis, Pernambuco, Northeast Brazil, 2014‐2017. Issue 8 (9th December 2019) - Guarines, Klarissa M.; Mendes, Renata P. G.; de Magalhães, Jurandy J. F.; Pena, Lindomar
Abstract: Norovirus (NoV) is currently the leading cause of nonbacterial gastroenteritis. In Brazil, few studies have characterized the molecular, epidemiological and clinical features of NoV‐associated gastroenteritis. This study aimed to describe the molecular and clinicoepidemiological findings of NoV infections in patients of all ages throughout Pernambuco state, Northeast Brazil. Thus, 1135 stool samples were analyzed from patients with gastroenteritis from Pernambuco state. NoV was detected by enzyme immunoassay in 125 (11.01%) samples. Regarding gender distribution, 55 (44.00%) patients were female and 70 (56.00%) male. Their ages ranged from 5 days to 87 years, and the group most affected by NoV infection (88.00%) was children under 3 years. Complete clinical information was available for 88 out of 125 NoV‐positive patients. Diarrhea was present in all patients and vomiting was reported in 60 patients (68.68%). Nine patients (10.22%) had bloody stools and 46 (52.27%) had a fever, with temperatures ranging from 37.90°C to 39.90°C (mean 38.20°C). NoV was detected mainly in the summer‐autumn seasons. Genome sequencing and phylogenetic analyses identified four different NoV GII genotypes circulating in this area of the country. Therefore, our study provided valuable information about the clinics and epidemiology of NoV infection in tropical settings and will assist health authorities to develop better control strategies against this important pathogen. Highlights: The clinicoepidemiological and molecular features of NoV infection in Northeast Brazil were characterized. Children under 3 years old were the age group most affected (88.00%). Four different NoV GII genotypes were found to be circulating in this area of the country.